Experience, heteroglosia and memory in Bruno Vvidal’s Rompan filas: figurines of horror as a fictional exercise (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
This test will analyze the book Rompan Filas (2016) of Bruno Vidal from three lines of sense, the allegory (Benjamin), the heteroglossia (Bajtín) and the subjective draft (Sarlo) to define the sway between the nominal thing and the poetical thing, the contradiction. This central aspect of this work will part from the allegory of horror as a problematizing element of the narrativity of traumatic experiences; the refraction of voices leads to heteroglossia, which carries  a responsibility as ethics of the text; finally, the prerogative filter will try to support the interstice between remembering and forgetting, between documentary and ficcional aspects.
Keywords: Chilean poetry; allegory; memory